THE PSYCHOLOGICAL PROFILE OF ADOLESCENTS WITH DIFFERENT TYPES OF ATTACHMENT TO THEIR PARENTS - Iana CIOBANU; Svetlana TOLSTAIA (Universitaria Publishing House, Craiova, 2022)
The article presents an analysis of the adolescent's personality from the perspective of the relationship formed with parents/peers, secure/insecure attachment and self-perception of masculine/feminine traits. The interaction and weighting and statistical analysis of the variables are also presented: trust, communication, sense of abandonment, extraversion, openness, consent, consistency, etc. For the first time, a correlation is made between the type of attachment to parents, peers and the type of relationship in adolescence. Investigations are carried out to identify whether or not there is interdependence between variables. The research was focused on studying the impact of parental attachment on relationships in adolescence. In the literature, adolescence is marked by critical changes in cognition, behavioral and emotional systems. Adolescents develop their own views and separate from their parents. Interpersonal relationships with parents play a primary role in the development of the person and the type of relationships he will later establish with other persons throughout life. The results show a positive correlation between the quality of attachment and the acceptable type of functional/social interaction between the research subjects and others. To develop the Psychological Profile of adolescents with secure/insecure attachment, the results of the diagnosis (block of 4 inventories) were used - 28 adolescents, aged between 16 and 19 years. The paper presents the profile of adolescents with secure/insecure attachment. The results of this study contribute to a better understanding of the role that attachment plays in the formation of relationships with others in the early age period.